Answer:
Step-by-step explanation:
Answer:
66.67 ml of 5% solution and 133.33 ml of 6.5% solution are mixed.
Step-by-step explanation:
Let 200 ml of 6% solution is formed by mixing x ml of 5% solution and y ml of 6.5% solution.
We can write the equation x + y = 200 ........ (1)
Now, x ml of 5% solution will contain ml of acid
Again, y ml of 6.5% solution will contain ml of acid.
So, mixing them together will give (0.05x + 0.065y) ml of acid in 200 ml of solution.
So, from the condition given we can write
⇒ 0.05x + 0.065y = 12
⇒ x + 1.3 y = 240 ........... (2) {Dividing both sides by 0.05}
Now, solving equations (1) and (2), we get
0.3y = (240 - 200) = 40
⇒ y = 133.33 ml
From equation (1) we get, x = 200 - 133.33 = 66.67 ml
Therefore, 66.67 ml of 5% solution and 133.33 ml of 6.5% solution are mixed. (Answer)
Answer:
The equation line is y + 3x = -10.
Step-by-step explanation:
In this question, first we have to find the slope of the equation:
The formula which we use to find the slope is:
slope = m = (y2-y1)/(x2-x1)
m = (8 + 1) / (-6 + 3)
m = 9 / (-3)
m = -3.
Now, put the value of slope and the first points (-3, -1). You can use any of the given points:
y - y1 = m(x - x1)
y + 1 = -3(x + 3)
y + 1 = -3x - 9
y + 3x = -10
This is the eqution line.
You can check if this line is true or not by putting the other points in this equation which will give the same points like,
y + 3(-6) = -10
y - 18 = -10
y = 8
So, we get the same old points (-6, 8) which we have given.
B. Triangle
C. Trapezoid
D. Rectangle
Answer:
D. Rectangle
Step-by-step explanation:
If you cut the pyramid with a plane parallel to the base, a square is obtained. If the plane is perpendicular to the base, you can obtain two different figures; if the plane passes through the vertex, a triangle is obtained, but if it doesn't pass through the vertex, a trapezoid is obtained.
Answer:
D. Rectangle
Step-by-step explanation:
Answer:
5y7777777777ewnaujhswfqasDAFfawtgshjyllu;9l8uky7jthrfh
Step-by-step explanation:
:)))))))))))))
Simplify both sides of the equation.
5x+2+6x+9=10x+5
(5x+6x)+(2+9)=10x+5(Combine Like Terms)
11x+11=10x+5
11x+11=10x+5
Subtract 10x from both sides.
11x+11−10x=10x+5−10x
x+11=5
Subtract 11 from both sides.
x+11−11=5−11
ANSWER: x=−6
5x+2+6x+9=10x+5
add like terms
11x + 11 = 10x + 5
11x + 11 - 11 = 10x + 5 - 11
11x = 10x - 6
11x - 10x = 10x - 10x - 6
x = -6 Answer